Technology in Medicine: Use of Artificial Intelligence, Robotics and Telemedicine in the Diagnosis and Treatment of Diseases - Riber Fabián Donoso Noroña; Nairovys Gómez Martínez; Adisnay Rodríguez Plasencia (Medisur)
Technology has come to revolutionize medicine, with a considerable improvement in the processes of diagnosis and treatment of diseases. Today, artificial intelligence, robotics and telemedicine are crucial tools in the development of modern medicine, allowing the implementation of innovative solutions to improve the quality of life of patients. The aim of the research was to describe the real impact, in an exhaustive manner, of the role of technology in medicine, by focusing on the implementation and effectiveness of artificial intelligence, robotics and telemedicine in the diagnosis and treatment of diseases. A search was carried out in important databases such as: Pubmed, Scielo, Lilacs, Cochrane Library and Web of Science. A total of 21 bibliographic references were obtained. In the field of medicine, the use of artificial intelligence can provide a wide range of benefits, such as improving the accuracy and speed of diagnosis, predicting disease outcomes and developing personalized treatments for patients. In surgery, robots can be used for minimally invasive surgical procedures and for remote surgery. Telemedicine offers care from a distance, enables real-time remote monitoring, and helps in the treatment of patients with chronic diseases. Technology is emerging as a powerful tool in healthcare.